Diagnostic Value and Safety of Brain Biopsy in Patients With Cryptogenic Neurological Disease: A Systematic Review and Meta-analysis of 831 Cases. Issue 2 (August 2015) - Bai, Harrison Xiao; Zou, Yingjie; Lee, Ashley M.; Lancaster, Eric; Yang, Li
Abstract : BACKGROUND: The role of brain biopsy in patients with cryptogenic neurological disease is uncertain. OBJECTIVE: To determine the risks and benefits of diagnostic brain biopsy for nonneoplastic indications in immunocompetent patients. METHODS: Appropriate studies were identified by searching electronic databases. RESULTS: We screened 3645 abstracts and included 20 studies with a total of 831 patients. Indications for biopsy were: (1a) severe neurological disease of unknown etiology in adults (n = 7) and (1b) in children (n = 2); (2) suspected primary angiitis of the central nervous system (PACNS) (n = 3); (3) chronic meningitis of unknown cause (n = 3); (4) atypical dementia (n = 4); and (5) nonneoplastic disease (n = 1). Diagnostic success rates calculated for subgroups were 51.3% (34.5-68.1) for 1a, 53.8% (42.9-64.5) for 1b, 74.7% (64.0-84.1) for 2, 30.3% (17.2-45.4) for 3, and 60.8% (41.2-78.8) for 4. Clinical impact rates were 30.5% (13.6-50.6) for 1a (n = 6), 67.1% (42.8-87.3) for 1b (n = 2), 8.3% (2.3-20.0) for 3 (n = 1), and 14.2% (6.5-24.3) for 4 (n = 2). Lymphoma (n = 32) and Creutzfeldt-Jakob disease (n = 30) were the most common diagnoses on the final histopathology reports of positive brain biopsies in 1a. In 1b, encephalitis (n = 7), PACNS (n = 6), and demyelination (n = 6) were the most common. The odds ratio for achieving a diagnostic biopsy when there was a radiological target was 3.70 ( P = .014, 95% confidence interval, 1.31-10.42). CONCLUSION: Brain biopsy in cryptogenic neurological disease was associated with the highest diagnostic yield in patients with suspected PACNS. The greatest clinical impact was seen in children with cryptogenic neurological disease. The presence of a radiological target was associated with a higher diagnostic yield. ABBREVIATIONS: CI, confidence interval CJD, Creutzfeldt-Jakob disease CNS, central nervous system PACNS, primary angiitis of the central nervous system RCVS, reversible cerebral vasoconstriction syndrome